Institutional dynamics and governance in transitions oriented towards sustainability - Tateishi, Henrique Ryosuke (2025)
A transition towards sustainability in our current agrifood system trajectories seems increasingly necessary in face of crises in multiple societal dimensions, from poverty, inequality and hunger, to climate change, biodiversity loss and deforestation. Yet, this sustainability, and what it may diversely signify and symbolise across contexts, rather seems but a distant promise. Sustainability Transitions Research field holds a normative orientation that regards to both understanding how to shift from persistent unsustainable trajectories into more sustainable ones, and how can actors influence on the governance of these changes. However, my hypothesis is that the normative contents of the sustainability of sustainability transitions research, in special the canonical literature, remained underexplored. On the one hand, this might signify an openness of the field to the pluralisation of sustainability meanings and representations, which enable knowledge and interpretive diversity. On the other hand, looming can be the risk of assuming a sustainability, which normative contents direct it towards universalising representations, replication, and acceleration of singular forms of framing unsustainability and sustainability. In reproducing integrative transitions knowledge, not only it assumes hegemonic forms of understanding transitions, but also suppresses alternatives that do not fit into these imaginaries. As such, reproducing much of the inequalities, inequities and other unsustainabilities that current agrifood trajectories, based on the normative contents of progress and modernization, locked us in. Hence, the objective of this thesis was to explore the influence of canonical Sustainability Transitions Research literature on knowledge integration or pluralisation of sustainability transitions interpretations. An institutional analysis was key in scrutinizing the diverse meanings of sustainability transitions, while a deeper look into institutional dynamics assisted in exploring the persistence of perceived unsustainabilities and openings towards sustainability representations. A systematic review based upon a reflexive methodological approach considered, as already interpreted secondary material, agrifood systems transitions cases studies that mobilised canonical transitions research. In this sense, cases studies were considered to manifest, in their interpretations, material for reflecting on the fields integrative knowledge direction or pluralising knowledge. In conclusion, canonical transitions research can be an entry point for pluralising sustainability transitions interpretations and knowledge. Further commitments in this orientation are bound to explore and disclose the normative contents, and ambivalences, of sustainability transitions, as systematically including it in the fields normative orientation (and positioning).